DIAGNOSIS OF MYXOBOLUS BRAMAE (MYXOSPOREA: MYXOBOLIDAE) IN THE KIDNEYS TISSUE OF CARASOBARBUS LUTEUS AND HISTOPATHOLOGICAL CHANGES ASSOCIATED WITH INFECTION - & et al., Mansoor (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted during the period from March till the end of October 2018, to study the histopathological changes of Myxobolus bramae in kidney tissue of Carasobarbus luteus caught from Tigris River passing through Baghdad city.  During the period of this study, a total of 60 fishes belonging to Carasobarbus luteus species from the family Cyprinidae were collected. The prevalence of infection with these protozoa was determinate (5.00%). Histopathological study due to M. bramae in the kidney tissue of C. luteus was done by using three types of stain: Hemotoxylin and eosin, giemsa and acid fast stain to observe plasmodia cyst and structures of spores. These changes characterized by tubular degeneration, necrosis, hyalinization of glomerular tuft, mild distension of Bowman᾿s space with a reduction in haemopoitic tissue together with inflammatory response, and accumulation of melanomacrophages at the site of infection. The results of this study revealed that Carasobarbus luteus from Tigris River at Baghdad city, it infected with Myxobolus bramae and this parasite cause severe histopathological changes in the infected kidneys tissue.